2009
DOI: 10.1175/2009jcli2848.1
|View full text |Cite
|
Sign up to set email alerts
|

North Pacific Gyre Oscillation Synchronizes Climate Fluctuations in the Eastern and Western Boundary Systems*

Abstract: Recent studies have identified the North Pacific Gyre Oscillation (NPGO) as a mode of climate variability that is linked to previously unexplained fluctuations of salinity, nutrient, and chlorophyll in the northeast Pacific. The NPGO reflects changes in strength of the central and eastern branches of the subtropical gyre and is driven by the atmosphere through the North Pacific Oscillation (NPO), the second dominant mode of sea level pressure variability in the North Pacific. It is shown that Rossby wave dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
150
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(160 citation statements)
references
References 34 publications
10
150
0
Order By: Relevance
“…Previous studies have shown that the NPGO can fluctuate on decadal time scales in observation, oceanalone model and the fully coupled model [e.g., Di Lorenzo et al, 2008Chhak et al, 2009;Ceballos et al, 2009;Furtado et al, 2011Furtado et al, , 2012. However, it is very difficult to tell whether the decadal variations of the observed NPGO are significant or not due to the lack of long-term observational records.…”
Section: Decadal Variability Of Npgo In Soda Reanalysis Datamentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that the NPGO can fluctuate on decadal time scales in observation, oceanalone model and the fully coupled model [e.g., Di Lorenzo et al, 2008Chhak et al, 2009;Ceballos et al, 2009;Furtado et al, 2011Furtado et al, , 2012. However, it is very difficult to tell whether the decadal variations of the observed NPGO are significant or not due to the lack of long-term observational records.…”
Section: Decadal Variability Of Npgo In Soda Reanalysis Datamentioning
confidence: 99%
“…The SLP variability associated with the NPGO features a NPO-like spatial pattern, characterized by a dipole structure over the North Pacific Ocean with an opposite sign north and south of 40 o N (Figure 1b). The coincidence of the dipole structure between the SSH and SLP implies that the NPGO mode is likely an oceanic expression of the atmospheric NPO-like forcing [Chhak et al, 2009;Ceballos et al, 2009;Furtado et al, 2011].It should be noted that since NPGO mode physically represents changes in the strength of To examine whether the NPGO has significant decadal variability in SODA, we perform a power spectrum analysis of the original time series of EOF2 (NPGO index, Figure 1c). The power spectrum features enhanced variance around 10-30 year band (significant at 95% confidence level), with a maximum at 18 years ( Figure 1d).…”
Section: Decadal Variability Of Npgo In Soda Reanalysis Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The intensified Aleutian low in the Warm/Pre-Cold phases imply cooling of the upper ocean in the western North Pacific caused by (cold) northerly winds and warming of the upper ocean towards the North American coast (left panels in Fig. 8), and an anomalous equatorward Ekman transport south of the Aleutian low (Ceballos et al 2009). The weakened Aleutian low in the Cold/Pre-Warm phases lead to a reversed forcing of the upper ocean (right panels in Fig.…”
Section: Surface Wind Stress Anomaliesmentioning
confidence: 99%